DNA shuffling to improve crude-water interfacial activity in biosurfactants with OmpA protein of Escherichia coli - Vanessa Lucía Nuñez Velez; Liseth Daniela Villamizar Gomez; Jhon E. Mendoza Ospina; Yasser Hayek-Orduz; Miguel Fernandez-Niño; Silvia Restrepo Restrepo; Óscar Alberto Álvarez Solano; Luis H. Reyes Barrios; Andres F. Gonzalez Barrios (PeerJ)
Surfactants are molecules derived primarily from petroleum that can reduce the surface tension at interfaces. Their slow degradation is a characteristic that could cause environmental issues. This and other factors contribute to the allure of biosurfactants today. Progress has been made in this area of research, which aims to satisfy the need for effective surfactants that are not harmful to the environment. In previous studies, we demonstrated the surface tension activity of the Escherichia coli transmembrane protein OmpA. Here, we carried out DNA shuffling on ompA to improve its interfacial activity. We evaluated changes in interfacial tension when exposing mutants to a water-oil interface to identify the most promising candidates. Two mutants reached an interfacial tension value lower (9.10 mN/m and 4.24 mN/m) than the original protein OmpA (14.98 mN/m). Since predicted isoelectric point values are far from neutral pH, the charge of the protein was a crucial factor in explaining the migration of proteins towards the interface. Low molecular weight mutants did not exhibit a significant difference in their migration to the interface.